An Analysis of Classroom Interaction in the Teaching-Learning Process of Speaking at Tenth Grade Students of Smk Al-Husain Keling in the Academic Year of 2017/2018 - Desi Annisa’ Ulan (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2017)
This thesis is entitled An Analysis of Classroom Interaction in Teaching-Learning Process of Speaking at Tenth Grade Student of SMK Al-Husain Keling I the Academic Year of 2017/2018. This study directs to find the teacher talk time and student talk time in teaching-learning process of speaking. The researcher used descriptive-quantitative method during the research since the aim of this study is to find out the classroom interaction in teaching learning process of speaking. Observation and interview used by the researcher to collect the data. The researcher also used Flander’s Interaction Analysis Category System (FIACS) in analyzing the data. The result of this research determine that the percentage of teacher’s talk was higher that students’ talk. It showed that the teacher’s talk was the most dominant classroom interaction during the observation. From the result the researcher concluded that the interaction would be active in teaching-learning process of speaking when the teacher and the students complemented each other.